2021
DOI: 10.1016/j.jhin.2021.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decrease of SARS-CoV-2 circulation in a large Italian hospital six weeks after the start of the immunization program

Abstract: Since the start of SARS-CoV-2 pandemic, clusters in hospital settings have been described worldwide. Therefore, healthcare workers (HCWs) are considered as a group at high risk of SARS-CoV-2 infection [1]. In Italy, in FebruaryeMay 2020, 119 doctors died because of COVID-19 and globally, in 2020, 91,270 COVID-19 cases were notified among HCWs, with a case-fatality rate of 0.2% [2]. On 27 th December 2020, the Italian Ministry of Health began the immunization campaign against SARS-CoV-2, targeting, as a priorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…On the one hand, this is a limitation of our study, on the other it is a strength in regards to the effectiveness of the application of prevention and protection measures in a pandemic context. Furthermore, in the near future, the reported data will be related to the benefits of the current vaccination campaign [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this is a limitation of our study, on the other it is a strength in regards to the effectiveness of the application of prevention and protection measures in a pandemic context. Furthermore, in the near future, the reported data will be related to the benefits of the current vaccination campaign [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, harder interventions such as mandatory vaccination policies or mandatory declination proved effective in reaching flu vaccination coverage in HCWs of over 90% [ 63 ]. Although a hard debate on mandatory flu vaccination for HCWs is long-standing and still in place [ 64 , 65 ], the extremely positive results obtained through mandatory COVID-19 vaccination for HCWs in Italy, both in terms of immunization rates (>98%) [ 66 ] and prevented infections [ 67 , 68 , 69 ], allow us to conclude that influenza vaccination coverage among HCWs would undoubtedly benefit from this policy.…”
Section: Discussionmentioning
confidence: 99%
“…As co-vaccination emerged as a promising tool to consolidate flu immunization rates [ 56 ], this should be firmly encouraged and persuaded, also through optimal logistical organization. Finally, given the unquestionable results, in terms of immunization rates and the mitigation of COVID-19 burden, achieved by mandatory COVID-19 vaccination for HCWs in Italy [ 66 , 67 , 68 , 69 ], also mandating influenza vaccination [ 63 ] would be another powerful if not decisive arrow in our quiver.…”
Section: Discussionmentioning
confidence: 99%
“…High transmission rate of SARS-CoV-2 poses healthcare workers at risk whenever they are in contact with infected patients. 1,2 Globally, healthcare workers (HCWs) constitute nearly 7% of all COVID-19 cases. 2 A prospective cohort study of a large healthcare worker population in the USA and UK revealed more than three times higher risk of infection amongst HCWs than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Globally, healthcare workers (HCWs) constitute nearly 7% of all COVID-19 cases. 2 A prospective cohort study of a large healthcare worker population in the USA and UK revealed more than three times higher risk of infection amongst HCWs than the general population. 3 In developing countries, the more HCWs get infected, the more disrupted health system will be.…”
Section: Introductionmentioning
confidence: 99%